2009
DOI: 10.1016/j.biopsych.2009.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Association of Attention-Deficit/Hyperactivity Disorder with a Candidate Region for Reading Disabilities on Chromosome 6p

Abstract: Overall this study supports a previous linkage study of ADHD indicating a risk gene for ADHD on 6p and points to VMP or DCDC2 as the most likely candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 57 publications
(132 reference statements)
1
43
1
1
Order By: Relevance
“…Replication of this SNP, along with expression and/or sequencing analyses to uncover its associated functional effects, would be desirable. We did not find significant support for association of reading and spelling with rs793862, the most widely genotyped polymorphism in DCDC2 association studies; though we did observe the same at-risk allele as in earlier studies 10,11,36,37 (the T-allele conferred a reading disadvantage of just 0.02 SD). Contradictory findings have been reported for this SNP: from nominally significant associations, 8,9 to associations specific only in the most severely affected families, 10 to the reverse effect (a nominally significant association in independent UK samples that disappeared when the sample was restricted to individuals with severe spelling difficulties 7 ), to no support for association of rs793862 to dyslexia in a cohort of US families.…”
Section: Discussioncontrasting
confidence: 51%
“…Replication of this SNP, along with expression and/or sequencing analyses to uncover its associated functional effects, would be desirable. We did not find significant support for association of reading and spelling with rs793862, the most widely genotyped polymorphism in DCDC2 association studies; though we did observe the same at-risk allele as in earlier studies 10,11,36,37 (the T-allele conferred a reading disadvantage of just 0.02 SD). Contradictory findings have been reported for this SNP: from nominally significant associations, 8,9 to associations specific only in the most severely affected families, 10 to the reverse effect (a nominally significant association in independent UK samples that disappeared when the sample was restricted to individuals with severe spelling difficulties 7 ), to no support for association of rs793862 to dyslexia in a cohort of US families.…”
Section: Discussioncontrasting
confidence: 51%
“…Both rs793862 and rs807701, and their haplotype, have also been tested in a sample of families with ADHD probands and also tested for reading measures, and revealed association with attentional phenotypes, but not the reading phenotypes. Although the association of rs793862 to DD or ADHD in four of the five studies appears to be with the minor allele [35,40,121,158], in the remaining British sample, it is with the major allele [80]. However, the association observed in this British sample is modest (P values from 0.02 to 0.04), suggesting it may be a type I error.…”
Section: Dyx2 On Chromosomementioning
confidence: 66%
“…Most of the genetic associations with dyslexia cluster around the 5' end of the KIAA0319 gene and generally show the same allelic trends across independent studies (Francks et al, 2004, Cope et al, 2005Schumacher et al, 2007;Luciano et al, 2007;Paracchini et al, 2008;Couto et al, 2009;Dennis et al, 2009;Wilcke et al, 2009). Francks et al (2004) identified 1 main RD risk haplotype comprising 3 SNPs (rs4504469, rs2038137, and rs2143340) with a frequency of 12% in families from the United Kingdom and the United States.…”
Section: Introductionmentioning
confidence: 73%